PENGEMBANGAN PERANGKAT PEMBELAJARAN BANGUN RUANG BERBANTUAN CABRI DAN WINGEOM UNTUK SISWA SEKOLAH MENENGAH PERTAMA - Rahajeng, Resty (Widya Warta, 2015)
It is a research on the development of a Cabri and Wingeom assisted solid geometry learning kit for the eighth year students of junior high school. The kit intended is a book containing a syllabus, a lesson plan for 9 meetings, a Cabri and Wingeom assisted student activity book consisting of 69 pages, and a learning achievement test in the form of multiple choice comprising 25 items.  Cabri program is used  to assist the learning on nets cubes, blocks, prisms, and pyramids. While, Wingeom program is used to help the learning on the properties, parts, surface areas and volume of cubes, blocks, prisms, and pyramids. The development research  employed  the 4D model which consists of four stages: (1) defining, (2) designing, (3) developing, and (4) disseminating. The subject for the research trial was 29 students and a math teacher of  junior high school. The techniques used to collect the data were validation sheets, observation sheets, questionnaires, and tests. The results of validity, practicality, and effectiveness were analyzed by converting quantitative data in the form of assessment scores into qualitative data in the form of a five scaled standard score. The products fulfilled valid, practical, and effective criteria. The validity of the products is apparent from the result of experts’ validation which showed that the products reached very valid criteria. The practicality of the products is apparent  from the results of the teacher assessment sheets which showed that the products reached very good criteria, and the observation sheets of learning process indicated that the percentage was in 96.03%. The effectiveness of the products is apparent from the result of the learning achievement test which showed that 93.1% of the students obtained the minimal score, namely 75 with the average score=84.55. While, the result of the questionnaire on the students’ interest reached good criteria with the average score=86.45.